Aspek Hukum Perlindungan Hak Kekayaan Intelektual di Industri Teknologi - Syarief, Amiroel Oemara; Pratiwi, Merina (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The rapid advancement of technology in the digital era presents new challenges for Intellectual Property Rights (IPR) protection, especially within the fast-evolving technology industry. Indonesia has enacted various regulations to safeguard IPR, such as the Copyright, Patent, and Trademark Laws. However, implementation within the technology sector faces significant challenges. This study aims to analyze the effectiveness of legal protection for IPR in the technology industry, identify existing challenges, and provide recommendations to strengthen IPR protection in Indonesia. The research employs normative legal methods with a juridical normative approach, where data is collected through a literature review of legislation, related documents, and scholarly literature. The findings reveal that while IPR regulations are in place, law enforcement remains weak due to limited infrastructure, low public awareness, and the complexity of new technologies like Artificial Intelligence (AI), blockchain, and Non-Fungible Tokens (NFTs), which are not yet accommodated by current regulations. Recommendations include strengthening regulations relevant to technological advancements, increasing public awareness of IPR importance, and leveraging digital technology to monitor IPR infringements. Effective IPR protection is expected to foster a conducive environment for innovation within Indonesia's technology industry.